Novel 4-in-1 strategy to combat colon cancer, drug resistance and cancer relapse utilizing functionalized bioinspiring lignin nanoparticle - Siddiqui, Lubna; Mishra, Harshita; Mishra, Pawan Kumar; Iqbal, Zeenat; Talegaonkar, Sushama (Medical hypotheses, 2018)
Colon cancer is one of the fatal forms of cancer all round the world with a equal frequency of occurrence in both male and female population. Mutational changes and defects in APC (Adenomatous Polyposis Coli) and DNA mismatch repair genes accompanied by genetic chaos in oncogenic pathways leads to colon cancer. Intensive study on pathogenesis of colon cancer has been made to decipher the mechanisms underlying the development and progress of the disease so as to develop effective treatment. However, a complete therapeutic regimen is still not available for combating this deadly disease. Hurdles faced by chemotherapy include drug resistance due to P-glycoprotein transporters, untoward effects on normal cells, high cost, bio-burden of the therapy, and the most dreadful drawback is cancer relapse. The concept of cancer relapse is related to development of oxidative stress that causes cell apoptosis. If the level of oxidative stress is inadequate to cause apoptosis then it leads to cell dormancy which may revive post chemotherapy. This hypothesis aims to put forward a combinatorial approach that includes utilizing a cost effective, biocompatible and environmentally benign nanoparticulate carrier made up of lignin, loaded with anti-cancer agent and P-gp modulator, and functionalized with ligand for CD44 receptors that are over expressed on cancer cells. Antioxidant effect of lignin will overcome dormancy of cancer cells making it possible for cell cycle specific drugs to kill them and prevent relapse and active targeting will prevent untoward effects on normal cells. Thus a robust and wholesome formulation can be developed to combat colon cancer.
Keywords: Caco-2 Cells; biosimilární léčivé přípravky; Cell Cycle; Rats; apoptóza; antigeny CD44; lignin; Antioxidants; Nanoparticles; Caco-2 buňky; DNA Mutational Analysis; Hyaluronan Receptors; Oxidative Stress; Neoplasm Recurrence, Local; oprava chybného párování bází DNA; mutační analýza DNA; lokální recidiva nádoru; Antineoplastic Agents; krysa rodu Rattus; ATP Binding Cassette Transporter, Subfamily B; buněčný cyklus; antioxidancia; chemorezistence; nádory tračníku; Multi drug resistance; DNA Mismatch Repair; protinádorové látky; zvířata; Biosimilar Pharmaceuticals; Drug Resistance, Neoplasm; Humans; Oxidative stress; Colonic Neoplasms; nanočástice; Cancer relapse; Risk; riziko; P-glykoproteiny; oxidační stres; CD44 receptors; Lignin; lidé; Apoptosis; Animals